Impact of Modifying Lazertinib Doses on Effectiveness and Safety in Patients With EGFR‐Positive Advanced Lung Cancer: A Multicenter, Prospective Observational Cohort Study - Mi‐Hyun Kim; Min Ki Lee; Ji Eun Park; Sun Hyo Park; Tae Won Jang; Chi Young Jung; Insu Kim; Seong Hoon Yoon; June Hong Ahn; Hyun‐Kyung Lee; Jin Han Park; Sun Ha Choi; et al. (Thoracic Cancer)
ABSTRACT Introduction The clinical application of lazertinib, a third‐generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, has extended to the treatment of EGFR‐mutant non‐small‐cell lung cancer (NSCLC); however, the effects of its dose modification on its efficacy and safety have not yet been adequately established. Methods This prospective, multicenter, observational cohort study aims to evaluate the clinical implications of adjusting the lazertinib dose. Patients will be categorized into two groups based on the lazertinib dose administered during the initial 12 weeks of treatment in routine clinical practice: 160 and 240 mg groups. The primary endpoints are progression‐free survival in the 160 mg group and identifying risk factors associated with dose modification during the 12‐week period. Discussion The findings from the present study will provide real‐world insights into the clinical factors leading to lazertinib dose adjustments and deepen our understanding of the efficacy and safety of lazertinib in patients with NSCLC. Our research will contribute toward optimizing medical strategies for NSCLC treatment and aid clinicians in making accurate clinical decisions regarding dose modifications in routine practice.